2017
DOI: 10.1088/1757-899x/226/1/012122
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of spatial resolution dependent variability in transcutaneous oxygen saturation using point spectroscopy system

Abstract: Abstract. This paper aims to investigate the variation in one's percent mean transcutaneous oxygen saturation (StO2) with differences in spatial resolution of data. This work required the knowledge of extinction coefficient of hemoglobin derivatives in the wavelength range of 520 -600 nm to solve for the StO2 value via an iterative fitting procedure. A pilot study was conducted on three healthy subjects with spectroscopic data collected from their right index finger at different arbitrarily selected distances.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…It also must be noted that the small fluctuation patterns in the inset of Fig. 2 (mean SD = 2.5 %) and the magnitudes of the observed values agreed considerably well with the reports of [12][13][14][15] that attributed the fluctuations to the oscillations in microcirculation system oxygen supply and metabolic mechanism. It is also found that the differences in the mean StO2 values of volunteers in Fig.…”
Section: Discussionsupporting
confidence: 87%
“…It also must be noted that the small fluctuation patterns in the inset of Fig. 2 (mean SD = 2.5 %) and the magnitudes of the observed values agreed considerably well with the reports of [12][13][14][15] that attributed the fluctuations to the oscillations in microcirculation system oxygen supply and metabolic mechanism. It is also found that the differences in the mean StO2 values of volunteers in Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The relationship between spatial separation and StO2 at five varying distances (i.e. 30 mm, 50 mm, 100 mm, 150 mm and 200 mm) was previously reported in [20]; the recorded results and the corresponding fitted linear line is shown in Figure 2. Based on the best fitted line in Figure 2, a normalization factor of 1.08 was calculated from the ratio of the value at 170 mm and 200 mm.…”
Section: Methodology 21 Multispectral Imaging Systemsupporting
confidence: 59%
“…These different experimental arrangements were made based on the position of the wound and for the convenience of the patients. It was reported in Philimon et al [20] that changes in the separation of skin region-detection system yielded different StO2 values. Since this experiment involved processing the spatially dependent reflected intensity of the multispectral images, a calibration procedure was necessary to normalize the measured reflectance from both samples.…”
Section: Methodology 21 Multispectral Imaging Systemmentioning
confidence: 97%
See 1 more Smart Citation
“…Since the system interrogates blood in dermal capillaries, arterioles and venules [14], the predicted value is often taken as the average of oxygen saturation within the cutaneous microenvironment, StO2. Previous works [15,16] from this laboratory found that the range of predictions is dependent on the system configuration and architecture, and the wavelengths used. Meanwhile the use of Artificial Intelligence (AI) techniques has received a great deal of attention in this arena of study over the past years due to its ability to learn by itself through a large set of data, events and statistics before making decision.…”
Section: Introductionmentioning
confidence: 99%